Effect of Spontaneous pushing during second stage of labor on delivery outcomes (Journal of Hama University, 2024)
Introduction: The second stage of labor represents a critical stage in the progress of childbirth with minimal complications for both the mother and the fetus, aiming to achieve the best outcomes for both. Pushing during this stage is considered important and necessary for the mother and the fetus, as it has potential positive and beneficial effects for both. Aim: Determine the effect of spontaneous payment during the second phase of labor on the product of birth. Material and Methods: a semi-experimental study was conducted on a random sample of 60 women who went through the second phase of labor, selected in a simple randomized manner in the labor and delivery department of the Assad Medical Complex in Hama governorate, and were randomly divided into two groups: A 30-woman experimental was left to the hospital routine (directed pushing application), a 30-woman control group (spontaneous pushing technique application), and the data was collected through three tools prepared for this purpose. Results: The findings of the study showed that the duration of the second phase of labor was longer and the number of payments during one shrink was greater in spontaneous payment compared to directed payment. The time taken during payment was shorter in spontaneous payment than in directed payment. The values of the newborn's Abgar hair were better and his need for incubator was lower in spontaneous payment than in directed payment, and the intensity of fatigue in spontaneous payment was lower in comparison with directed payment. It also showed that there are no significant differences between spontaneous and guided payment in terms of fetal pulse rate, traceability of amniotic fluid, episiotomy procedure, bleeding amount, newborn breastfeeding ability, perineal ruptures, and in terms of the ability to breastfeed and carry a newborn and form a safety ball. Conclusion and Recommendations: Adopt the spontaneous payment method in the second phase of labor besides the directed payment method within the hospital policy in the generation of ladies, educate midwives around, and conduct a study on a larger sample